1996
DOI: 10.1152/jappl.1996.81.3.1051
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary blood flow distribution in standing horses is not dominated by gravity

Abstract: Recent studies using microspheres in dogs, pigs and goats have demonstrated considerable heterogeneity of pulmonary perfusion within isogravitational planes. These studies demonstrate a minimal role of gravity in determining pulmonary blood flow distribution. To test whether a gravitational gradient would be more apparent in an animal with large vertical lung height, we measured perfusion heterogeneity in horses (vertical lung height = approximately 55 cm). Four unanesthetized Thoroughbred geldings (422-500 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 0 publications
11
94
0
1
Order By: Relevance
“…Our selection of 15-m-diameter microspheres for the present study was influenced by previous reports examining the distribution of pulmonary blood flow in resting and exercising horses with this technique (2,6,21). However, in these reports, intrapulmonary arteriovenous shunting of 15-m-diameter microspheres was not examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our selection of 15-m-diameter microspheres for the present study was influenced by previous reports examining the distribution of pulmonary blood flow in resting and exercising horses with this technique (2,6,21). However, in these reports, intrapulmonary arteriovenous shunting of 15-m-diameter microspheres was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these reports, intrapulmonary arteriovenous shunting of 15-m-diameter microspheres was not examined. Although, in these experiments, cardiac (2,6,21) and other tissues may have been removed at necropsy, investigators did not report on the absence/presence of intravenously injected microspheres in the heart and/or other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The latter mechanism was considered as true as intuitively it was thought that the change in gravity direction will affect the lung perfusion in the same way, i.e., less perfusion towards dorsal lung regions, now non-dependent, in the prone position. Several experiments found that the dorsal lung regions when in the prone position still had the highest amount of blood flowing through them (2)(3)(4)(5)(6)(7)(8). Therefore, this unexpected finding argued against the second mechanism to explain the reduction in intra-pulmonary shunt.…”
Section: Rationalementioning
confidence: 99%
“…With similar techniques yielding greater spatial resolution Glenny et al (Glenny et al, 1991) were able to quantify the contribution of gravitational heterogeneity to overall perfusion heterogeneity and concluded that gravity was a minor factor in the distribution of Q. Hlastala et al (Hlastala et al, 1996) using the same technique found that differences in flow at the same gravitational level could be 10 times greater than the difference in flow at different levels. Pulmonary perfusion has been studied in both humans and animals under microgravity conditions induced by parabolic flight.…”
Section: Isogravitational Heterogeneitymentioning
confidence: 99%